Exposure to Community Violence and Sexual Behaviors Among African American Youth: Testing Multiple Pathways. Issue 1 (2nd January 2018) - Voisin, Dexter R.; Hotton, Anna; Neilands, Torsten
ABSTRACT: African American youth bear a disproportionate burden of sexually transmitted infections. A growing number of studies document that youth exposure to community violence and sexual behaviors are highly correlated. Despite such growing evidence, only a few studies have empirically tested conceptually driven pathways that may account for such relationships. This study seeks to address that gap by exploring multiple pathways linking exposure to community violence and youth sexual behaviors. Using an existing sample of 563 African American youth attending high school, we examined whether possible links between exposure to community violence and sexual activity, sexual risk behaviors were mediated by aggression, low student-teacher connectedness, and negative peer norms. Major findings indicated indirect relationships between exposures to community violence and both sexual activity and risky sex, mediated by aggression and negative peer norms with no significant differences based on gender or socioeconomic status. Overall findings also indicated a significant indirect effect of aggression to risky sex via negative peer norms and from community violence to risky peer norms via aggression. By illuminating ways that community violence, aggression, peer norms, and sexual behaviors are dynamically interrelated, these findings have significant implications for future research and intervention initiatives aimed at addressing the different pathways.